Vector modeling in pedagogical research on problems of physical education and sports - Manzheley I.V. ,; Zagrevskaya A.I. , (Theory and Practice of Physical Culture, 2024)
Abstract Objective of the study was to describe the capabilities of the vector modeling method in pedagogical research in physical education and sports. Results and conclusions. The article presents a description of the vector modeling method. An overview of the dialectical-logical algorithm of the vector modeling method is given. The systematization of pedagogical models of physical education has been carried out. Health-adaptive, socially-oriented, personality-oriented and sports-recreational models of physical education are identified and analyzed. Their specific features, advantages and limitations in the practice of physical education are described. The prospects for using the vector modeling method in humanities research are shown.